A renewed call for conservation leadership 10 years further in the feral cat Trap‐Neuter‐Return debate and new opportunities for constructive dialogue. Issue 4 (1st February 2022) - Debrot, Adolphe O.; Ruijter, Martin N. M.; Endarwin, Wempy; van Hooft, Pim; Wulf, Kai; Delnevo, Adrian J.
Abstract: It has been 10 years since a seminal paper in the journal Conservation Biology called for stronger leadership from the conservation community in countering the growing inappropriate use of Trap‐Neuter‐Return (TNR) as a method to control feral cat, Felis catus, populations. The practice is rapidly spreading to areas of wildlife and conservation significance, and the need to counter this development is extremely urgent. So far, the promulgation of TNR has been based on a narrow, single‐species approach to animal welfare. However, a new, yet little‐noticed, species‐inclusive perspective on animal welfare includes the consideration of collateral animal suffering for a more equitable assessment of TNR. Each setting, depending on the level of conservation required, may call for different methods for the management of free‐roaming cats. TNR is just one such method and its appropriateness depends on the specific wildlife conservation needs for each area specified.